Prosthetic valve endocarditis caused by Pasteurella in a penicillin allergic patient: challenges in diagnosis and treatment - Giovanni Satta; Rebecca Louise Gorton; Hala Kandil (MDPI AG, 2012)
Pasteurella multocida is a rare cause of infective endocarditis with only a few cases described. This report involves a 38-year-old penicillin-allergic patient in an immunocompromised state with several co-morbidities. Two molecular microbiological techniques, 16S rRNA sequencing and matrix-assisted laser desorption/ionization time-of-flight mass spectrometry were used to confirm the species identification as P. multocida. Previous reports in the literature are also reviewed.